Improving the methodology for assessing the sustainable development of municipalities - M. V. Kukarin; V. V. Rokotyanskaya (Вестник университета)
The purpose of the article is to assess the level of sustainable development of municipalities and improve the assessment methodology by taking into account the budget sustainability index. The paper defines the concept of sustainable development of a municipality as a process of managing the ecologio-socio-economic system of a municipality that ensure the integral stability of the structure, elements and their connections. The current state of the urban districts of the Republic of Bashkortostan in dynamics in the period from 2015 to 2019 is analysed, the level of sustainability of municipal districts is assessed according to indicators of economic, environmental and social subsystems. The assessment methodology is supplemented by the following indicators of the budget subsystem: overall budget stability; budget deficit/surplus; total solvency; the ratio of accounts payable and local budget expenditures; the ratio of municipal debt and revenue; the level of budget balance.